LINGUISTIC AND SOCIOLOGICAL PARAMETERS OF GENDER COMMUNICATION IN ADVERTISING DISCOURSE (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes advertising texts from both linguistic and sociological perspectives in the context of gender communication. Advertising text is not merely a simple medium for promoting a product or service; it is also a profound socio-cultural phenomenon. From a linguistic point of view, an advertisement incorporates all levels of language — lexical, syntactic, pragmatic, and stylistic features — while also reflecting the culture, values, social norms, and stereotypes of the society.        Through advertising texts, social stereotypes, elements of intercultural communication, gender-specific language used for men and women, powerful persuasive mechanisms, and layers of meaning are revealed. The study conducts lexical, stylistic, and pragmatic analysis based on examples from Western and local advertisements, also considering instances of code-switching. Furthermore, it explores how cultural values, social context, and communicative goals are expressed through advertising language. The visual and verbal construction of male and female images demonstrates how gender roles are shaped. In conclusion, the significance of advertising language in shaping modern trends and gender-based social consciousness is substantiated.